Intorno a Boccaccio / Boccaccio e dintorni 2016 Atti del Seminario internazionale di studi (Certaldo Alta, Casa di Giovanni Boccaccio, 9 settembre 2016) - Zamponi, Stefano (Studi e saggi, 2017)
The work 'Intorno a Boccaccio/Boccaccio e dintorni 2016' is the outcome of the international seminar held in Certaldo on September 16, 2017, promoted by the ENGB National Association (Ente Nazionale Giovanni Boccaccio) and now in its third edition. The seminar, which is now held on an annual basis, has the main purpose of giving visibility to young scholars, allowing them to present new and ongoing researches. Alongside philological and critical contributions related to Decameron and its Fortleben, this work is characterized by the attention it pays to other works by Boccaccio (Filostrato, Rime, De mulieribus claris, Epistole, Trattatello), examined under the aspect of textual tradition, rhetorical figures and lexicon.